PENGARUH MINAT DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI DI SMA SWASTA TAMANSISWA PEMATANGSIANTAR - Jelita Silitonga; Debby Petra Meyana Sitorus (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to determine the effect of interest and learning discipline on the economic learning outcomes of XI social studies class students at Tamansiswa Private High School. the variables in this study are interest and learning discipline as independent variables and economic learning outcomes as the dependent variable.This type of research is quantitative research with a quantitative descriptive data analysis approach.The research subjects were XI social studies class students at Tamansiswa Private High School Pematangsiantar totaling 127 people.This study used saturated sampling techniques.Data collection techniques using instruments: (1) questionnaire of interest in learning, (2) questionnaire of learning discipline, and (3) learning outcomes in the form of final semester test scores in Economics subjects.The results of this study indicate that: (1) there is a positive and significant effect of interest in learning on learning outcomes, this result can be seen in the t test where the calculated t value of interest in learning (4.028) > the t table value (1.97928) which means that the variable is significant. (2) there is a positive and significant effect of learning discipline on learning outcomes, this result can be seen in the t test where the tcount value of learning discipline (3.169) > the ttable value (1.97928) which means that the variable is significant. (3) interest in learning and learning discipline together affect learning outcomes, this result can be seen in the F test where the Fcount value (14.955) > than the Ftable value (3.07). The R Square coefficient of determination test is known to be 0.194, which means that 19.4% of the variables of interest in learning and learning discipline affect the economic learning outcomes of XI social studies class students at Tamansiswa Pematangsiantar Private High School and the remaining 80.6% is the influence of other variables not examined in this study.